Application of silica gel to immobilise iodine waste by low-temperature sintering. (1st February 2021) - Wei, Guilin; Shu, Xiaoyan; Zhang, Zhentao; Han, Wenhong; Luo, Fen; Liu, Yi; Yang, Jingjun; Li, Bingsheng; Xie, Yi; Wang, Lan; Lu, Xirui
ABSTRACT : The disposal of radioactive iodine waste is a top priority for the nuclear industry. This work mainly studies the replacement of crystalline material (SiO2 ) in silicate-based material with amorphous material (silica gel) to immobilise iodine waste at low-sintering temperatures. The results show that under low-temperature sintering conditions, B2 O3 –Bi2 O3 –ZnO–silica gel is more suitable than B2 O3 –Bi2 O3 –ZnO–SiO2 for immobilising iodine waste because the former one has a higher amorphous index and density than the latter. This novel insight can improve the disposal of radioactive waste at low-sintering temperatures.